2018
DOI: 10.1186/s12936-018-2588-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Plasmodium species responsible for malaria reveals Plasmodium vivax isolates in Duffy negative individuals from southwestern Nigeria

Abstract: BackgroundMalaria in Nigeria is principally due to Plasmodium falciparum and, to a lesser extent to Plasmodium malariae and Plasmodium ovale. Plasmodium vivax is thought to be absent in Nigeria in particular and sub-Saharan Africa in general, due to the near fixation of the Duffy negative gene in this population. Nevertheless, there are frequent reports of P. vivax infection in Duffy negative individuals in the sub-region, including reports from two countries sharing border with Nigeria to the west (Republic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 60 publications
(75 reference statements)
1
62
1
Order By: Relevance
“…This concurs with the higher prevalence of P. malariae infections in older age groups reported in Papua New Guinea using similarly sensitive molecular method -post-PCR ligase detection reaction-fluorescent microsphere assay (LDR-FMA) compared with light microscopy (21). The results herein adds to data on prevalence of non-falciparum species in Nigeria which remains scanty (22)(23)(24)(25) given the focus on P. falciparum. With the push for global eradication it buttresses the proponent that other human Plasmodium species should be brought to focus and included in malaria elimination strategies.…”
Section: Discussionsupporting
confidence: 83%
“…This concurs with the higher prevalence of P. malariae infections in older age groups reported in Papua New Guinea using similarly sensitive molecular method -post-PCR ligase detection reaction-fluorescent microsphere assay (LDR-FMA) compared with light microscopy (21). The results herein adds to data on prevalence of non-falciparum species in Nigeria which remains scanty (22)(23)(24)(25) given the focus on P. falciparum. With the push for global eradication it buttresses the proponent that other human Plasmodium species should be brought to focus and included in malaria elimination strategies.…”
Section: Discussionsupporting
confidence: 83%
“…The absence of P. vivax cases was expected, as this species is rarely encountered in West Africa [1]. However, two recent studies documented significant carriage of P. vivax DNA and/or antibodies against P. vivax proteins in some West African individuals; therefore, testing for this species has significant value [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ethiopia, a malaria-endemic country, revealed that the overall prevalence rate of malaria detected by microscopy was 18.4% [18]. The molecular detection of malaria parasite in Democratic Republic of Congo and Nigeria demonstrated that the infection rate of the disease was 34.9% [8] and 58.7% respectively [10].…”
Section: Discussionmentioning
confidence: 99%
“…PCR has also been helpful in the differential detection of all malaria parasites up to species levels, thereby revealing the high prevalence of mixed infections [1,9]. The application of sensitive methods such as PCR to determine the prevalence of Plasmodium species will allow better documentation of malaria epidemiology [10] and overcome the lack of knowledge on the prevalence of malaria infection in the displaced population. This study was proposed to determine the molecular prevalence of malaria parasites amongst symptomatic patients in Ardamata IDP camp, Al-Geneina City, Sudan.…”
Section: Introductionmentioning
confidence: 99%